Suggestion of Tunisia's medical oncologist in the management of breast cancer during COVID-19 pandemic. (October 2020) - Yahyaoui, Yosra; Ghodhbani, Zahra; Hamdi, Adel; Letaief, Feryel; Zenzri, Yosr; Ben Said, Azza; Blouza, Imen; Mezlini, Amel
Cancer patients are at higher risk to be infected with COVID-19 and to develop a more severe form. Breast cancer (BC) treatments, including chemotherapy (CT), targeted therapy and immunotherapy can weaken the immune system and possibly cause lung problems. For all these reasons Salah Azaiez Institute's department of Medical Oncology took drastic actions to protect patients. In this article we will discuss protocol adjustments taken during the COVID-19 pandemic for breast cancer patients.